A topologically distinct class of photolyases specific for UV lesions within single-stranded DNA. Issue 22 (3rd December 2020) - Emmerich, Hans-Joachim; Saft, Martin; Schneider, Leonie; Kock, Dennis; Batschauer, Alfred; Essen, Lars-Oliver
Abstract: Photolyases are ubiquitously occurring flavoproteins for catalyzing photo repair of UV-induced DNA damages. All photolyases described so far have a bilobal architecture with a C-terminal domain comprising flavin adenine dinucleotide (FAD) as catalytic cofactor and an N-terminal domain capable of harboring an additional antenna chromophore. Using sequence-similarity network analysis we discovered a novel subgroup of the photolyase/cryptochrome superfamily (PCSf), the NewPHLs. NewPHL occur in bacteria and have an inverted topology with an N-terminal catalytic domain and a C-terminal domain for sealing the FAD binding site from solvent access. By characterizing two NewPHL we show a photochemistry characteristic of other PCSf members as well as light-dependent repair of CPD lesions. Given their common specificity towards single-stranded DNA many bacterial species use NewPHL as a substitute for DASH-type photolyases. Given their simplified architecture and function we suggest that NewPHL are close to the evolutionary origin of the PCSf.